P‐15: Student Poster: Charge Trap‐Based Synaptic Transistor Employing In‐Ga‐Zn‐O as Channel and Trap Layers for Bio‐Inspired Neuromorphic Computing. Issue 1 (28th June 2022) - Park, Junhyeong; Jang, Yuseong; Lee, Jinkyu; Lee, Soo-Yeon
Abstract : In this paper, indium‐gallium‐zinc‐oxide (IGZO) based charge trap synaptic transistors with Al2 O3 /IGZO/Al2 O3 gate dielectric stacks were proposed. It was found that the annealing effect of the IGZO charge trap layer is one of the key parameters for an excellent memory window and program/erase operations without light stimuli. Synaptic behaviors such as excitatory post‐synaptic current (EPSC), inhibitory post‐synaptic current (IPSC), long‐term potentiation (LTP), and long‐term depression (LTD) are success‐fully implemented.